Pathological Findings in the Pituitary Glands of Dogs and Cats. Issue 6 (November 2018) - Polledo, Laura; Grinwis, Guy C. M.; Graham, Peter; Dunning, Mark; Baiker, Kerstin
With the exception of classic functional adenomas in dogs and horses, pituitary lesions are infrequently described in the veterinary literature. Approximately 10% of pituitary glands from asymptomatic humans contain abnormalities, but the equivalent proportion in small animals is unknown. Pituitary glands from 136 dogs and 65 cats collected during routine necropsies were examined to determine the prevalence of pituitary lesions and their histopathological diagnosis. Lesions were characterized in sections stained with hematoxylin and eosin, periodic acid-Schiff (PAS), Gordon and Sweet's and reticulin stains, and immunohistochemistry for adrenocorticotropic hormone (ACTH), growth hormone, melanocyte stimulating hormone–α, and prolactin. Pituitary abnormalities were identified in 36 of 136 (26.4%) dogs and 10 of 65 (15.3%) cats. Cystic changes were the most common lesion, occurring in 18 (13.2%) dogs and 8 (12.3%) cats. Pituitary neoplasia was detected in 14.1% (12/85) of middle-aged and old dogs; 1 (1.5%) cat had pituitary nodular hyperplasia. PAS and reticulin stains helped differentiate ACTH-immunoreactive adenomas from hyperplastic nodules: adenomas contained PAS-positive intracytoplasmic granules and loss of the normal reticulin network. One dog had a pituitary carcinoma with infiltration into the thalamus. Other pituitary abnormalities included secondary metastases (2 dogs) and hypophysitis (4 dogs, 1 cat). In most cases, the lesion appeared to be subclinical and could be considered incidental, whereas clinical manifestations were apparent in only 4 dogs (2.9%) and none of the cats with pituitary lesions. Pituitary abnormalities are common in dogs and cats, and their clinical relevance requires further investigation.